2022
DOI: 10.1161/strokeaha.121.037750
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Neuropsychological Deficits in First-Ever Isolated Ischemic Thalamic Stroke and Their Association With Stroke Topography: A Case-Control Study

Abstract: Background: The thalamus plays an essential role in cognition. Cognitive deficits have to date mostly been studied retrospectively in chronic thalamic stroke in small cohorts. Studies prospectively evaluating the evolution of cognitive deficits and their association with thalamic stroke topography are lacking. This knowledge is relevant for targeted patient diagnostics and rehabilitation. Methods: Thirty-seven patients (57.5±17.5 [mean±SD] years, 57% me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…As one possible reason for these discrepancies, it was suggested that besides the severity, the location of WMH might be an important determinant of cognitive impairment [6,7]. For example, small lesions in the thalamus can strongly affect cognition [8], while widely distributed deep WMH can remain clinically silent [9]. In addition to being followed by different cognitive consequences, different locations of WMH might be influenced by different pathomechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…As one possible reason for these discrepancies, it was suggested that besides the severity, the location of WMH might be an important determinant of cognitive impairment [6,7]. For example, small lesions in the thalamus can strongly affect cognition [8], while widely distributed deep WMH can remain clinically silent [9]. In addition to being followed by different cognitive consequences, different locations of WMH might be influenced by different pathomechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…After any stroke, rehabilitation is fundamental and can critically impact the patient’s recovery 21–23. Targeted neurorehabilitation programmes are particularly effective, as demonstrated in our case 23 24. To date, solid scientific evidence emphasises how intensive rehabilitation programmes should be started as soon as possible, although 24 hours after the stroke.…”
Section: Discussionmentioning
confidence: 84%
“…Besides rehabilitation, other factors that shape the prognosis of thalamic strokes are (1) the extent of the damaged thalamic territory, which affects the amount of altered connections24; (2) the location of the stroke, which affects the quality of the damaged connections24 and (3) secondary prevention strategies 29 30. Although the first two factors are relevant to classify the clinical features and implementing a tailored neurorehabilitation programme, ‘classical’ risk factors should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…In their fully adjusted models, infarct in the thalamus more than quadrupled the risk of cognitive decline among these patients. A recent study further characterized cognitive recovery among patients with ischemic thalamic stroke: in this case control study with a 2-year follow-up period, patients with anterior and inferolateral thalamic strokes were found to have poorer recovery of language, memory, and executive function than those with paramedian strokes ( 42 ).…”
Section: Neuroimaging Modalities Used As Biomarkers For Cognitive Rec...mentioning
confidence: 95%